Proteotransciptomics of the Most Popular Host Sea Anemone Entacmaea quadricolor Reveals Not All Toxin Genes Expressed by Tentacles Are Recruited into Its Venom Arsenal - Cassie M. Hoepner; Zachary K. Stewart; Robert Qiao; Emily K. Fobert; Peter J. Prentis; Alex Colella; Tim Chataway; Karen Burke da Silva; Catherine A. Abbott (Toxins, 2024)
While the unique symbiotic relationship between anemonefishes and sea anemones is iconic, it is still not fully understood how anemonefishes can withstand and thrive within the venomous environment of their host sea anemone. In this study, we used a proteotranscriptomics approach to elucidate the proteinaceous toxin repertoire from the most common host sea anemone, Entacmaea quadricolor. Although 1251 different toxin or toxin-like RNA transcripts were expressed in E. quadricolor tentacles (0.05% of gene clusters, 1.8% of expression) and 5375 proteins were detected in milked venom, only 4% of proteins detected in venom were putative toxins (230), and they only represent on average 14% of the normalised protein expression in the milked venom samples. Thus, most proteins in milked venom do not appear to have a toxin function. This work raises the perils of defining a dominant venom phenotype based on transcriptomics data alone in sea anemones, as we found that the dominant venom phenotype differs between the transcriptome and proteome abundance data. E. quadricolor venom contains a mixture of toxin-like proteins of unknown and known function. A newly identified toxin protein family, Z3, rich in conserved cysteines of unknown function, was the most abundant at the RNA transcript and protein levels. The venom was also rich in toxins from the Protease S1, Kunitz-type and PLA2 toxin protein families and contains toxins from eight venom categories. Exploring the intricate venom toxin components in other host sea anemones will be crucial for improving our understanding of how anemonefish adapt to the venomous environment.